Why Pitch Sensitivity Matters: Event-Related Potential Evidence of Metric and Syntactic Violation Detection Among Spanish Late Learners of German - Schmidt-Kassow, Maren; Roncaglia-Denissen, M. Paula; Kotz, Sonja A. (Frontiers in Psychology, 2011)
Event-related potential (ERP) data in monolingual German speakers have shown that sentential metric expectancy violations elicit a biphasic ERP pattern consisting of an anterior negativity and a posterior positivity (P600). This pattern is comparable to that elicited by syntactic violations. However, proficient French late learners of German do not detect violations of metric expectancy in German. They also show qualitatively and quantitatively different ERP responses to metric and syntactic violations. We followed up the questions whether (1) latter evidence results from a potential pitch cue insensitivity in speech segmentation in French speakers, or (2) if the result is founded in rhythmic language differences. Therefore, we tested Spanish late learners of German, as Spanish, contrary to French, uses pitch as a segmentation cue even though the basic segmentation unit is the same in French and Spanish (i.e., the syllable). We report ERP responses showing that Spanish L2 learners are sensitive to syntactic as well as metric violations in German sentences independent of attention to task in a P600 response. Overall, the behavioral performance resembles that of German native speakers. The current data suggest that Spanish L2 learners are able to extract metric units (trochee) in their L2 (German) even though their basic segmentation unit in Spanish is the syllable. In addition Spanish in contrast to French L2 learners of German are sensitive to syntactic violations indicating a tight link between syntactic and metric competence. This finding emphasizes the relevant role of metric cues not only in L2 prosodic but also in syntactic processing.